Effect of Realistic Mathematics Education Approach on Visual Mathematics Literacy Perceptions and Problem Solving Attitude of Students - Emel Çilingir, Perihan Dinç Artut (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The aim of study was to investigate the effects of Realistic Mathematics Education (RME) based instruction in the elementary mathematics curriculum on the mathematics achievement, Visual Mathematics Literacy Self Efficiency Perceptions (VMLSP) and Mathematics Problem Solving Attitude (MPSA). The study was determined as a quasi-experimental study which conducted as a pre-posttest design with a control group. The research was conducted with 147 students at fourth grade of a public elementary school in Adana. In the study, the experimental group and one of the control group were instructed by one of the researchers, while in other control group was instructed by their teacher. ‘Geometric Shapes’ unit was instructed with RME at the experimental group while the current instructional method was conducted to the control groups. The data were obtained with mathematics achievement tests and VMLSP and MPSA Scale which provided goodness according to the confirmatory factor analysis model. The quantitative data was evaluated by using mixed ANOVA and t-Test methods. As a result, it was found that the students at the experimental group have more successful in mathematic achievement tests and more progress on VMLSP and MPSA than control group.